MnS / MXene composite aerogel material with three-dimensional heterostructure as well as preparation method and application of MnS / MXene composite aerogel material
By growing MNS nanomaterials in situ on the MXENE matrix and forming a three -dimensional pore structure, the three -dimensional heterogeneous structure MNS/MXENE composite gas gel material is prepared to solve the problem of limited dynamic dynamics and side reactions of MNS positive pole materials. Application of high -performance positive materials.
Patent Information
- Application Number
- CN202411448060.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-21
AI Technical Summary
The reaction kinetics of MnS positive electrode materials are limited and have high reaction potential, resulting in limited initial capacity and irreversible side reactions.
By growing MNS nanomaterials in situ on the MXENE matrix, and forming a three -dimensional pore structure through the cross -linked agent, the three -dimensional heterogeneous structure MNS/MXENE composite gas gel material is prepared.
This composite gas gel material has a stable structure, large ratio area and rich activity sites. As the application of the positive pole material, it shows high reversible capacity, excellent multiplier performance, good cycle life and low impedance.
Smart Images

Figure CN119330403A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cathode materials, and more specifically, to a three-dimensional heterostructured MnS / MXene composite aerogel material and a preparation method and application thereof. Background Art
[0002] Aqueous zinc-based energy storage devices such as zinc-ion batteries and zinc-ion hybrid capacitors have gradually become a research hotspot in the field of energy storage in recent years due to their low cost, high safety, suitable redox potential (-0.763V vs. SHE) and considerable theoretical capacity (820mAh / g). In this context, the design and optimization of positive electrode materials are crucial to improving the overall performance of aqueous zinc-based energy storage devices. MnS positive electrode materials have attracted much attention in the field of energy storage due to their high conductivity and excellent thermal stability. However, as a wide-bandgap p-type semiconductor with moderate electronic conductivity (3.1eV), MnS has limited reaction kinetics and high reaction potential, which leads to limited initial capacity and irreversible side reactions during initial activation.
[0003] Therefore, how to inhibit the dissolution and volume change of MnS cathode materials and promote their rapid activation has become the key to developing high-performance MnS cathodes. Summary of the invention
[0004] Based on the above technical problems existing in the prior art, the present invention provides a method for preparing a three-dimensional heterogeneous structure MnS / MXene composite aerogel material. In this method, MnS nanomaterials are in situ grown on a MXene substrate and a three-dimensional porous structure is formed through a cross-linking agent. The obtained composite aerogel material has a stable structure, a large specific surface area and abundant active sites. When used as a cathode material, it exhibits excellent electrochemical properties.
[0005] In order to achieve the above object, the technical solution of the present invention is as follows:
[0006] A method for preparing a three-dimensional heterogeneous structure MnS / MXene composite aerogel material comprises the following steps:
[0007] A sulfur source, a manganese source and a cross-linking agent are added to the MXene solution, mixed evenly, and then a hydrothermal reaction is carried out under protective gas conditions. After the reaction is completed, the solution is washed and dried to obtain the MnS / MXene composite aerogel.
[0008] In some embodiments, the temperature of the hydrothermal reaction is 120-200°C.
[0009] In some embodiments, the molar ratio of the sulfur source to the manganese source is 1-2:1; specifically, the molar ratio of sulfur to manganese is 1-2:1.
[0010] In some embodiments, the cross-linking agent is at least one of ethylenediamine, butanediol, and polydopamine.
[0011] In some embodiments, the sulfur source is at least one of L-cysteine, thiourea, and thioacetamide.
[0012] In some embodiments, the manganese source is at least one of manganese chloride, manganese sulfate, and manganese acetate.
[0013] In some embodiments, the MXene solution is prepared by etching the MAX phase precursor with HF generated in situ by HCl and LiF, followed by centrifugation and ultrasonic stripping. Specifically, the following steps are included: first, LiF and HCl are stirred in a reaction vessel to ensure that LiF is completely dissolved in HCl; next, the MAX phase is added to the mixed solution in multiple times, and the mixture is continuously stirred and etched at 30-60°C for 24-60h; after the reaction is completed, the obtained product is repeatedly washed with HCl and deionized water by centrifugation until the upper liquid becomes turbid and reaches a pH value of about 6-7; then, the solution is transferred to a washing bottle, ultrasonically treated under argon protection (20min), and finally centrifuged to collect the upper centrifuge liquid, which is the prepared MXene solution.
[0014] In some embodiments, the MAX phase has a general chemical formula of M n+1 AX n The general chemical formula of MXene is M n+1 X n T x , wherein M is a transition metal element, A is an aluminum element, X is a carbon or nitrogen element, T is various surface groups on the outer surface of the transition metal layer, and n is 1, 2 or 3. Preferably, MXene is M2XT x 、M3X2T x 、M4X3T x At least one of; specifically, the transition metal element is one or more of Ti, V, Cr, and Mo, and the surface group is one or more of OH, F, and Cl.
[0015] In some embodiments, the concentration of the MXene solution is 10-20 mg / mL.
[0016] In some embodiments, the hydrothermal reaction time is 6-12 hours.
[0017] In some embodiments, the protective gas is at least one of argon, helium, and nitrogen.
[0018] In some embodiments, the drying process uses at least one of room temperature drying, vacuum drying or freeze drying.
[0019] In some embodiments, the preparation method comprises the following steps:
[0020] A sulfur source, a manganese source and a cross-linking agent are added to the MXene solution, mixed evenly, and then a hydrothermal reaction is carried out under protective gas conditions. After the reaction is completed, the solution is washed by dialysis and dried to obtain the MnS / MXene composite aerogel material.
[0021] In some embodiments, the dialysis wash time is 12-24 hours.
[0022] The present invention also provides a MnS / MXene composite aerogel material, which is prepared by the preparation method of any of the above embodiments. The composite aerogel material has a three-dimensional porous structure and is rich in sulfur vacancies, and MnS nanomaterials are distributed on the surface of the MXene material.
[0023] The present invention also provides a positive electrode material, which includes the above-mentioned MnS / MXene composite aerogel material.
[0024] The present invention also provides a positive electrode, which comprises the positive electrode material mentioned above.
[0025] The present invention also provides a zinc-based energy storage device, which includes the above-mentioned positive electrode. Specifically, the zinc-based energy storage device is an aqueous zinc-based energy storage device, including but not limited to a zinc ion battery and a zinc ion hybrid capacitor.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The present invention adopts a one-step hydrothermal method to in-situ grow MnS nanomaterials on a MXene material matrix in a specific reaction system. The average particle size of the nanomaterial is only 10-100 nm, and a three-dimensional network cross-linked structure is formed in combination with a cross-linking agent. This not only makes the obtained composite aerogel have a stable structure, but also has a large specific surface area and abundant active sites.
[0028] The method of the present invention modifies the MnS positive electrode material to obtain a three-dimensional heterostructured MnS / MXene composite aerogel material rich in sulfur vacancies, which is used as a positive electrode material in an aqueous zinc-based energy storage device, showing high reversible capacity, excellent rate performance, good cycle life and low impedance, which not only optimizes the positive and negative electrode capacity matching of the energy storage device, but also effectively improves the energy density and power density of the energy storage device, thereby improving its electrochemical performance.
[0029] The composite aerogel material obtained by the method of the present invention has practical application potential in the field of zinc-based energy storage and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The front view and stereogram of the three-dimensional heterostructured MnS / MXene composite aerogel material obtained in Example 1 of the present invention;
[0031] Figure 2 This is a FESEM image of the three-dimensional heterogeneous structure MnS / MXene composite aerogel material obtained in Example 1 of the present invention;
[0032] Figure 3 TEM image of the three-dimensional heterostructured MnS / MXene composite aerogel material obtained in Example 1 of the present invention;
[0033] Figure 4 This is the XRD pattern of the three-dimensional heterostructured MnS / MXene composite aerogel material obtained in Example 1 of the present invention;
[0034] Figure 5 The three-dimensional heterogeneous structure MnS / MXene composite aerogel material obtained in Example 1 of the present invention is used as a positive electrode material to assemble the electrochemical performance test diagram of a zinc ion battery; wherein (a) is a constant current charge and discharge test diagram; (b) is a rate performance test diagram; (c) is a Ragone diagram; (d) is an electrochemical impedance test diagram; (e) is a cycle performance test diagram at a current density of 0.1A / g; (f) is a cycle performance test diagram at a current density of 1.0A / g;
[0035] Figure 6 The three-dimensional heterogeneous structure MnS / MXene composite aerogel material obtained in Example 1 of the present invention is used as a positive electrode material to assemble the electrochemical performance test diagram of the zinc ion hybrid capacitor; wherein, (a) and (b) are constant current charge and discharge test diagrams; (c) is a rate performance test diagram; (d) is a Ragone diagram; (e) is an electrochemical impedance test diagram; (f) is a cycle performance test diagram at a current density of 1.0 A / g;
[0036] Figure 7 The figures are electrochemical performance test graphs of zinc ion batteries assembled with the MnS / MXene composite material obtained in Comparative Example 1 as the positive electrode material; wherein, (a) is a constant current charge and discharge test graph; (b) is a rate performance test graph; (c) is a Ragone graph; (d) is an electrochemical impedance test graph; (e) is a cycle performance test graph at a current density of 0.1 A / g; and (f) is a cycle performance test graph at a current density of 1.0 A / g. DETAILED DESCRIPTION
[0037] Many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar modifications without violating the connotation of the present invention, so the present invention is not limited to the specific implementation disclosed below.
[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0039] The preparation method of the MXene solution used in the following examples and comparative examples comprises the following steps:
[0040] LiF and HCl were stirred in a reaction vessel to completely dissolve LiF in HCl. Ti3AlC2 was then added to the mixed solution in multiple times and etched at 40°C for 48 hours with continuous stirring. After the reaction was completed, the obtained product was repeatedly washed with HCl and deionized water by centrifugation until the upper liquid became turbid and reached a pH value of about 6-7. The solution was then transferred to a washing bottle and subjected to ultrasonic treatment (20 minutes) under argon protection. Finally, the upper centrifuge liquid was collected by centrifugation to obtain a MXene solution.
[0041] Example 1
[0042] A method for preparing a three-dimensional heterogeneous structure MnS / MXene composite aerogel material comprises the following steps:
[0043] Manganese acetate and thioacetamide (the molar ratio of sulfur to manganese is 1:1) are dispersed in 5 mL of a 20 mg / mL MXene solution and mixed, and then 100 μL of ethylenediamine is added and ultrasonicated for 20 min (100 W, 40 kHz); then the temperature is raised to 180 ° C under argon protection for hydrothermal reaction for 12 h to obtain a three-dimensional heterogeneous structure MnS / MXene composite hydrogel rich in sulfur vacancies; the hydrogel is dialyzed and washed for 24 h and then freeze-dried to obtain a three-dimensional heterogeneous structure MnS / MXene composite aerogel material rich in sulfur vacancies.
[0044] The obtained composite aerogel was characterized and the results are as follows Figure 1-Figure 4 shown.
[0045] Figure 1 Digital photo of a three-dimensional heterostructured MnS / MXene composite aerogel rich in sulfur vacancies. Figure 1 It can be clearly seen that the composite aerogel has a three-dimensional structure.
[0046] Figure 2This is the FESEM image of the three-dimensional heterostructured MnS / MXene composite aerogel rich in sulfur vacancies. It can be seen that the porous structure of the aerogel presents a large active specific surface area.
[0047] Figure 3 This is the TEM image of the three-dimensional heterostructured MnS / MXene composite aerogel rich in sulfur vacancies. It can be clearly seen that the MnS nanocrystals distributed on the MXene aerogel have an average particle size of 10 to 100 nm.
[0048] Figure 4 This is the XRD pattern of the three-dimensional heterostructured MnS / MXene composite aerogel rich in sulfur vacancies. It can be seen from the figure that it has the characteristic peaks of both MnS and MXene without other impurities.
[0049] The composite aerogel prepared in this example was used as the positive electrode material to prepare the positive electrode sheet, which was assembled into a zinc ion battery and a zinc ion capacitor, respectively. The electrochemical properties of the battery and the capacitor were then tested. The test results were as follows: Figure 5 and Figure 6 shown.
[0050] like Figure 5 As shown, the zinc ion battery prepared by using the composite aerogel prepared in this embodiment as the positive electrode material exhibits high reversible specific capacities of 425.9, 415.2, 387.0, 345.8, 263.9, 215.5, 135.5 and 97.3 mAh / g at current densities of 0.1, 0.2, 0.3, 0.5, 1.0, 2.0, 3.0 and 5.0 A / g, respectively; at a high power density of 7848.0 W / Kg, it exhibits an energy density of 130.8 Wh / Kg; after 100 cycles at a current density of 0.1 A / g, the capacity retention rate is 82.3%; after 1000 cycles at a current density of 1.0 A / g, the capacity retention rate is 86.2%.
[0051] like Figure 6 As shown, the composite aerogel prepared in this embodiment is used as a positive electrode material to prepare a zinc ion capacitor, which exhibits high reversible specific capacities of 293.1, 276.7, 256.5, 225.3, 190.8, 158.1, 119.7, 95.3 and 77.1 F / g at current densities of 0.1, 0.2, 0.3, 0.5, 1.0, 2.0, 3.0, 5.0 and 10.0 A / g, respectively; at a power density of 100 W / Kg, it exhibits a high energy density of 165.8 Wh / Kg; and after 10,000 cycles at a current density of 1.0 A / g, the capacity retention rate is 82.3%.
[0052] Depend on Figure 5 and Figure 6It can be seen that the composite aerogel prepared in this embodiment has high energy density and power density, excellent rate performance, good cycle life, high coulombic efficiency and low impedance.
[0053] Example 2
[0054] A method for preparing a three-dimensional heterogeneous structure MnS / MXene composite aerogel material comprises the following steps:
[0055] Manganese acetate and L-cysteine (the molar ratio of sulfur to manganese is 1:1) were dispersed into 5 mL of 20 mg / mL MXene solution and mixed, and then 100 μL of ethylenediamine was added and ultrasonicated for 20 min (100 W, 40 kHz); then the temperature was raised to 180 °C under argon protection for hydrothermal reaction for 12 h to obtain a three-dimensional heterostructured MnS / MXene composite hydrogel rich in sulfur vacancies; the hydrogel was dialyzed and washed for 24 h and then freeze-dried to obtain a three-dimensional heterostructured MnS / MXene composite aerogel material rich in sulfur vacancies.
[0056] Example 3
[0057] A method for preparing a three-dimensional heterogeneous structure MnS / MXene composite aerogel material comprises the following steps:
[0058] Manganese chloride and thioacetamide (the molar ratio of sulfur to manganese is 1:1) were dispersed into 5 mL of 20 mg / mL MXene solution and mixed, and then 100 μL of ethylenediamine was added and ultrasonicated for 20 min (100 W, 40 kHz); then the temperature was raised to 180 °C under argon protection for hydrothermal reaction for 12 h to obtain a three-dimensional heterostructured MnS / MXene composite hydrogel rich in sulfur vacancies; the hydrogel was dialyzed and washed for 24 h and then freeze-dried to obtain a three-dimensional heterostructured MnS / MXene composite aerogel material rich in sulfur vacancies.
[0059] Example 4
[0060] A method for preparing a three-dimensional heterogeneous structure MnS / MXene composite aerogel material comprises the following steps:
[0061] Manganese acetate and thioacetamide (the molar ratio of sulfur and manganese is 2:1) were dispersed into 5 mL of 20 mg / mL MXene solution and mixed, and then 100 μL of ethylenediamine was added and ultrasonicated for 20 min (100 W, 40 kHz); then the temperature was raised to 180 °C under argon protection for hydrothermal reaction for 12 h, and the MnS / MXene composite aerogel was obtained after dialysis and washing for 24 h and freeze-drying.
[0062] Example 5
[0063] A method for preparing a three-dimensional heterogeneous structure MnS / MXene composite aerogel material comprises the following steps:
[0064] Manganese acetate and thioacetamide (the molar ratio of sulfur to manganese is 1:1) are dispersed in 5 mL of a 10 mg / mL MXene solution and mixed, and then 100 μL of ethylenediamine is added and ultrasonicated for 20 min (100 W, 40 kHz); then the temperature is raised to 180 ° C under argon protection for hydrothermal reaction for 12 h to obtain a three-dimensional heterostructure MnS / MXene composite hydrogel rich in sulfur vacancies; the hydrogel is dialyzed and washed for 24 h and then freeze-dried to obtain a three-dimensional heterostructure MnS / MXene composite aerogel material rich in sulfur vacancies.
[0065] Example 6
[0066] A method for preparing a three-dimensional heterogeneous structure MnS / MXene composite aerogel material comprises the following steps:
[0067] Manganese acetate and thioacetamide (the molar ratio of sulfur to manganese is 1:1) are dispersed in 5 mL of 20 mg / mL MXene solution and mixed, and then 100 μL of polydopamine is added and ultrasonicated for 20 min (100 W, 40 kHz); the temperature is raised to 180 ° C under argon protection for hydrothermal reaction for 12 h to obtain a three-dimensional heterogeneous structure MnS / MXene composite hydrogel rich in sulfur vacancies; the hydrogel is dialyzed and washed for 24 h and then freeze-dried to obtain a three-dimensional heterogeneous structure MnS / MXene composite aerogel material rich in sulfur vacancies.
[0068] Example 7
[0069] A method for preparing a three-dimensional heterogeneous structure MnS / MXene composite aerogel material comprises the following steps:
[0070] Manganese acetate and thioacetamide (the molar ratio of sulfur to manganese is 1:1) were dispersed into 5 mL of 20 mg / mL MXene solution and mixed, and then 100 μL of ethylenediamine was added and ultrasonicated for 20 min (100 W, 40 kHz); then the temperature was raised to 120 °C under argon protection for hydrothermal reaction for 12 h to obtain a three-dimensional heterostructured MnS / MXene composite hydrogel rich in sulfur vacancies; the hydrogel was dialyzed and washed for 24 h and then freeze-dried to obtain a three-dimensional heterostructured MnS / MXene composite aerogel material rich in sulfur vacancies.
[0071] Example 8
[0072] A method for preparing a three-dimensional heterogeneous structure MnS / MXene composite aerogel material comprises the following steps:
[0073] Manganese acetate and thioacetamide (the molar ratio of sulfur to manganese is 1:1) are dispersed in 5 mL of a 20 mg / mL MXene solution and mixed, and then 100 μL of ethylenediamine is added and ultrasonicated for 20 min (100 W, 40 kHz); then the temperature is raised to 180 ° C under argon protection for hydrothermal reaction for 6 h to obtain a three-dimensional heterogeneous structure MnS / MXene composite hydrogel rich in sulfur vacancies; the hydrogel is dialyzed and washed for 24 h and then freeze-dried to obtain a three-dimensional heterogeneous structure MnS / MXene composite aerogel material rich in sulfur vacancies.
[0074] Example 9
[0075] A method for preparing a three-dimensional heterogeneous structure MnS / MXene composite aerogel material comprises the following steps:
[0076] Manganese acetate and thioacetamide (the molar ratio of sulfur to manganese is 1:1) were dispersed into 5 mL of 20 mg / mL MXene solution and mixed, and then 100 μL of ethylenediamine was added and ultrasonicated for 20 min (100 W, 40 kHz); then, a hydrothermal reaction was carried out at 180 °C for 12 h under argon protection to obtain a three-dimensional heterostructured MnS / MXene composite hydrogel rich in sulfur vacancies; the hydrogel was dialyzed and washed for 12 h and then freeze-dried to obtain a three-dimensional heterostructured MnS / MXene composite aerogel material rich in sulfur vacancies.
[0077] Example 10
[0078] A method for preparing a three-dimensional heterogeneous structure MnS / MXene composite aerogel material comprises the following steps:
[0079] Manganese acetate and thioacetamide (the molar ratio of sulfur to manganese is 1:1) were dispersed into 5 mL of 20 mg / mL MXene solution and mixed, and then 100 μL of ethylenediamine was added and ultrasonicated for 20 min (100 W, 40 kHz); then, a hydrothermal reaction was carried out at 180 °C for 12 h under argon protection to obtain a three-dimensional heterostructured MnS / MXene composite hydrogel rich in sulfur vacancies; the hydrogel was dialyzed and washed for 24 h and then vacuum dried to obtain a three-dimensional heterostructured MnS / MXene composite aerogel rich in sulfur vacancies.
[0080] Comparative Example 1
[0081] A method for preparing a heterogeneous structure MnS / MXene composite material comprises the following steps:
[0082] Manganese acetate and thioacetamide (in a sulfur-manganese ratio of 1:1) were dispersed into 5 mL of MXene solution (20 mg ml -1), ultrasonically treated for 20 min (100 W, 40 kHz), and then heated to 180 ° C under argon protection for hydrothermal reaction for 12 h. After the reaction, dialyzed and washed for 24 h and then freeze-dried to obtain the MnS / MXene composite material.
[0083] The composite aerogel prepared in this comparative example was used as the positive electrode material to prepare the positive electrode sheet, which was assembled into a zinc ion battery, and then the electrochemical performance of the battery was tested. The test results are as follows: Figure 7 shown.
[0084] like Figure 7 As shown, the zinc ion battery prepared by using the composite material prepared in this comparative example as the positive electrode material exhibits a reversible specific capacity of 366.2, 317.8, 289.1, 246.6, 165.0 and 97.7 mAh / g at current densities of 0.1, 0.2, 0.3, 0.5, 1.0 and 2.0 A / g, respectively; at a power density of 1978.2 W / Kg, it exhibits an energy density of 134.9 Wh / Kg; after 100 cycles at a current density of 0.1 A / g, the capacity retention rate is 46.70%; after 1000 cycles at a current density of 1.0 A / g, the capacity retention rate is 49.46%.
[0085] This shows that the composite aerogel prepared in the present invention exhibits more excellent electrochemical performance.
[0086] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0087] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a three-dimensional heterostructured MnS / MXene composite aerogel material, characterized in that: The following steps are involved: A sulfur source, a manganese source and a cross-linking agent are added to the MXene solution, mixed evenly, and then a hydrothermal reaction is carried out under protective gas conditions. After the reaction is completed, the solution is washed and dried to obtain the MnS / MXene composite aerogel.
2. The method for preparing the three-dimensional heterostructured MnS / MXene composite aerogel cathode material according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 120-200°C.
3. The method for preparing the three-dimensional heterostructured MnS / MXene composite aerogel material according to claim 1, characterized in that: The molar ratio of the sulfur source to the manganese source is 1-2:
1.
4. The method for preparing the three-dimensional heterostructured MnS / MXene composite aerogel material according to claim 1, characterized in that: The cross-linking agent is at least one of ethylenediamine, butanediol, and polydopamine; and / or the sulfur source is at least one of L-cysteine, thiourea, and thioacetamide; and / or the manganese source is at least one of manganese chloride, manganese sulfate, and manganese acetate.
5. The method for preparing the three-dimensional heterostructured MnS / MXene composite aerogel material according to claim 1, characterized in that: The concentration of MXene solution is 10-20 mg / mL.
6. The method for preparing the three-dimensional heterostructured MnS / MXene composite aerogel material according to claim 1, characterized in that: The hydrothermal reaction time is 6-12h.
7. A MnS / MXene composite aerogel material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 6; the composite aerogel material has a three-dimensional porous structure and is rich in sulfur vacancies, and the MnS nanomaterial is distributed on the surface of the MXene material.
8. A positive electrode material, characterized in that Including the MnS / MXene composite aerogel material as described in claim 7.
9. A positive electrode, characterized in that Comprising the positive electrode material as claimed in claim 8.
10. A zinc-based energy storage device, characterized in that: Comprising the positive electrode as claimed in claim 9.